2018
DOI: 10.1136/bcr-2018-224992
|View full text |Cite
|
Sign up to set email alerts
|

Pleural tuberculosis: a key differential diagnosis for pleural thickening, even without obvious risk factors for tuberculosis in a low incidence setting

Abstract: We report the case of a 64-year-old woman, presenting with pleuritic chest pain and weight loss. She had a previous history of breast malignancy and no clear risk factors for tuberculosis (TB). Initial investigations showed a right-sided pleural effusion and pleural thickening suggestive of malignancy, which would have been in keeping with the clinical presentation. Initial pleural biopsy showed features suggestive of possible TB infection, though no growth on cultures. A repeat biopsy was negative on initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…As observed in our patient's case, pleural effusions caused by tuberculosis often manifest as moderately sized, predominantly right-sided, and unilateral [ 6 ]. Pleural effusions caused by tuberculosis can be challenging to diagnose, especially when lung parenchymal disease is absent on imaging.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…As observed in our patient's case, pleural effusions caused by tuberculosis often manifest as moderately sized, predominantly right-sided, and unilateral [ 6 ]. Pleural effusions caused by tuberculosis can be challenging to diagnose, especially when lung parenchymal disease is absent on imaging.…”
Section: Discussionmentioning
confidence: 71%
“…Tuberculous pleural effusions often resolve spontaneously but may lead to active tuberculosis in up to two-thirds of cases. Therefore, a high index of suspicion is crucial to diagnosing individuals exhibiting characteristics associated with pleural tuberculosis during the window of opportunity for intervention [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical therapy (PT) typically manifests unilaterally and may vary in size. [2] In the examination of a substantial population, it was shown that pleural fluid was present exclusively on the left side in 38.1% of cases, exclusively on the right side in 48.4% of cases, and both sides were affected in 13.5% of cases. The most commonly observed symptoms include a non-productive cough, occurring in around 70% of cases, and pleuritic chest pain, also reported in approximately 70% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…There is a scarcity of published data about the management of pleural tuberculosis accompanied by tuberculous pyomyositis. [2]…”
Section: Introductionmentioning
confidence: 99%